The Effect of Physical Exercise on Functional Capacity and Perception of Well-Being in Older Adults - Ingrid J. Sánchez-Roa; Javier L. Reina-Monroy; Clara S. Juliao-Vargas; Luis A. Cardozo (OVS LLC, 2024)
Study purpose. The study aimed to evaluate the effect of strength training exercises on functional capacity, quality of life and perception of well-being in elderly people. Materials and Methods. It was used a mixed study with sequential explanatory design, in which 25 elderly females between 62 and 85 years participated in a physical exercise program for eight weeks, with a frequency of 3 days and sessions of 58 minutes on average. The Senior Fitness Test battery of test item was conducted with a grip strength test, heart rate monitoring in a 6-minute test, SF-36 health questionnaire and post-intervention focus group oriented to well-being analysis. Results. Cardiorespiratory capacities, strength and flexibility improved significantly (p< .05), but agility and heart rate did not change (p> .05). Scores increased in the 8 quality of life dimensions analyzed, and in subjective well-being, health improvement was identified in both the self-perception and autonomy of daily activities related to vitality, motivation, social interaction and adherence to physical activity. The findings indicate that physical exercise based on strength training improves functional capacity, health-related quality of life and the well-being of seniors. Conclusions. The findings of this study show that eight weeks of physical exercise based on strength training with affordable means (own body weight, elastic bands and dumbbells) with a frequency of 3 days a week, contribute to improving the functional capacity of strength and flexibility in upper and lower limbs, and cardiorespiratory endurance in older females. This intervention was also found to have a positive impact on quality of life, as well as on the perception of well-being.